Importance of behavior in response to tinnitus symptoms - Savastano, M; Maron, M B (The international tinnitus journal, 1999)
Among subjects affected by tinnitus, two groups are distinguished: patients who can cope positively with the symptom and patients who cannot cope with it. These differing attitudes suggest the necessity to study affected patients' "illness behavior" (i.e., a subjective interpretation of symptoms concerning body functioning). Our study considered 125 idiopathic tinnitus sufferers who requested a visit by an otorhinolaryngologist expressly for this symptom. All patients were invited to complete the illness behavior questionnaire (IBQ). IBQ mean score results were lower for affective inhibition and irritability and resulted in higher denial. Patients with more psychological suffering presented higher levels of hypochondria, disease convinction, and dysphoria. Results revealed a correlation between psychological suffering and tinnitus intensity: The group of patients with stronger psychological suffering included more subjects with a higher intensity level. The other group included more subjects with a moderate intensity level. Within the psychological evaluation of tinnitus sufferers, the IBQ results demonstrated particular sensitivity in revealing patients' nonadaptation area in coping with the symptom.